The cellular prion protein and its derived fragments in human prion diseases and their role as potential biomarkers. (2nd November 2019) - Thüne, Katrin; Schmitz, Matthias; Villar-Piqué, Anna; Altmeppen, Hermann Clemens; Schlomm, Markus; Zafar, Saima; Glatzel, Markus; Llorens, Franc; Zerr, Inga
ABSTRACT: Introduction : Human prion diseases are a heterogeneous group of incurable and debilitating conditions characterized by a progressive degeneration of the central nervous system. The conformational changes of the cellular prion protein and its formation into an abnormal isoform, spongiform degeneration, neuronal loss, and neuroinflammation are central to prion disease pathogenesis. It has been postulated that truncated variants of aggregation-prone proteins are implicated in neurodegenerative mechanisms. An increasing body of evidence indicates that proteolytic fragments and truncated variants of the prion protein are formed and accumulated in the brain of prion disease patients. These prion protein variants provide a high degree of relevance to disease pathology and diagnosis. Areas covered : In the present review, we summarize the current knowledge on the occurrence of truncated prion protein species and their potential roles in pathophysiological states during prion diseases progression. In addition, we discuss their usability as a diagnostic biomarker in prion diseases. Expert opinion : Either as a primary factor in the formation of prion diseases or as a consequence from neuropathological affection, abnormal prion protein variants and fragments may provide independent information about mechanisms of prion conversion, pathological states, or disease progression.